Frau Holliger könne Hebamme sein, aber soll von Doktor Häggy nichts lernen: Als das Fricktal seine Hebammen in die Schule schicken sollte - Fäs, Sophie (Avisos de Viena, 2025)
At birth, life and death are sometimes close together: a new life is about to enter our world. At the same time, the mother's life is sometimes in danger. From the 18th century onwards, the enlightened absolutist states, including the Habsburg monarchy, made it their explicit aim to better protect mothers and children. In the course of an all-encompassing health reform in 1770, obstetrics was to be improved throughout the empire. But what does improved mean? For the enlightened absolutist thinkers in Vienna, this meant, among other things, placing the training of midwives in the hands of doctors. They had promised the authorities that having the midwives trained by physicians would reduce tragic deaths. A promise that the Habsburg monarchy, which was dependent on a healthy population, was happy to accept. In many rural areas, however, these measures were not at all well received. This was also the case in the Further Austrian Fricktal, an area far away from Vienna. But why did the population resist proposals that seemed so plausible in Vienna, and wit what success did the rural population stand up against the unpopular reform of midwifery training?